Vertical 1T‐TaS2 Synthesis on Nanoporous Gold for High‐Performance Electrocatalytic Applications. Issue 15 (7th March 2018) - Huan, Yahuan; Shi, Jianping; Zou, Xiaolong; Gong, Yue; Zhang, Zhepeng; Li, Minghua; Zhao, Liyun; Xu, Runzhang; Jiang, Shaolong; Zhou, Xiebo; Hong, Min; Xie, Chunyu; et al.
Abstract: 2D metallic TaS2 is acting as an ideal platform for exploring fundamental physical issues (superconductivity, charge‐density wave, etc.) and for engineering novel applications in energy‐related fields. The batch synthesis of high‐quality TaS2 nanosheets with a specific phase is crucial for such issues. Herein, the successful synthesis of novel vertically oriented 1T‐TaS2 nanosheets on nanoporous gold substrates is reported, via a facile chemical vapor deposition route. By virtue of the abundant edge sites and excellent electrical transport property, such vertical 1T‐TaS2 is employed as high‐efficiency electrocatalysts in the hydrogen evolution reaction, featured with rather low Tafel slopes ≈67–82 mV dec −1 and an ultrahigh exchange current density ≈67.61 µA cm −2 . The influence of phase states of 1T‐ and 2H‐TaS2 on the catalytic activity is also discussed with the combination of density functional theory calculations. This work hereby provides fundamental insights into the controllable syntheses and electrocatalytic applications of vertical 1T‐TaS2 nanosheets achieved through the substrate engineering. Abstract : Vertically oriented 1T‐TaS2 nanosheets are first synthesized on nanoporous gold (NPG) substrates, via the chemical vapor deposition route. By virtue of the abundant edge sites and excellent electrical transport property, such vertical 1T‐TaS2 /NPG are employed as high‐efficiency electrocatalysts in the hydrogen evolution reaction. The influence of the phase states of TaS2 on the catalytic activity is also explored according to theoretical calculations.